Research on optimization design of high-performance manufactured sand concrete material composition in seasonal frozen areas - Huang, Chuan; Zhu, Junxian; Rong, Hongliu; Yang, Xiaolong (Frontiers in Materials, 2025)
To address the issues of shrinkage cracking and durability in manufactured sand concrete in seasonally frozen regions, silica fume, fly ash, and superabsorbent polymer (SAP) were selected to prepare high-performance manufactured sand concrete. This study innovatively integrates SAP with fly ash and silica fume through a three-factor, four-level orthogonal experiment, systematically revealing their synergistic effects on workability, mechanical properties, and frost resistance—a gap in existing research. The results indicate that SAP improves the fluidity, workability, and slump of the concrete but reduces its mechanical properties. In contrast, silica fume and fly ash enhance the mechanical properties of the concrete. Notably, SAP’s dual role in mitigating shrinkage (via internal curing) and frost damage (by pore structure optimization) is quantitatively established, with a 0.18% dosage reducing drying shrinkage by 13.4% and extending freeze-thaw resistance to 300 cycles. The optimized mix proportion for high-performance manufactured sand concrete is: water-to-cement ratio of 0.37, sand ratio of 42%, SAP content of 0.18%, silica fume content of 0.00%, and fly ash content of 15%. This study fills a research gap by quantitatively establishing the effects of SAP, fly ash, and silica fume on concrete performance in cold climates.